ISLAMIC BANKING: PROBLEMS, SOLUTIONS AND PROSPECTIVES (World Economics and Finance Bulletin, 2023)
This article reveals the role and importance of Islamic finance and banking in the world economy. In particular, the article focuses on the structure of Islamic banking, the form of management, the impact on the state economy, some problems and solutions in the field of Islamic banking. Analysis of a new promising direction in the field of banking and finance - Islamic banking on the example of Uzbekistan